2014
DOI: 10.1108/jocm-05-2014-0102
|View full text |Cite
|
Sign up to set email alerts
|

Media portrayals of older employees: a success story?

Abstract: Purpose – The purpose of this paper is to provide an analysis of how portrayals of older employees in mass media messages can help combating stereotypical beliefs on their employability. Design/methodology/approach – The authors conducted a systematic review of empirical studies on mass media portrayals of older employees in order to show what these reveal about the ways in which their employment status, occupation, job type, or work set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…This relates especially to negative competence media stereotypes. A more balanced portrayal of older employees’ competences might help to counter stereotypical beliefs about this group (Van Selm and Van der Heijden 2014). For example, media could emphasise that individual skills and health are of greater importance to job performance than age (Posthuma and Campion 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This relates especially to negative competence media stereotypes. A more balanced portrayal of older employees’ competences might help to counter stereotypical beliefs about this group (Van Selm and Van der Heijden 2014). For example, media could emphasise that individual skills and health are of greater importance to job performance than age (Posthuma and Campion 2009).…”
Section: Discussionmentioning
confidence: 99%
“…By investigating both corporate and news media, this study considers the two key domains in which the consequences of stereotypical portrayals of older workers are likely being most significant. First, stereotypes in corporate media are likely to reflect inter-organisational beliefs (Van Selm and Van der Heijden 2014) and inform (older) employees and organisational stakeholders about how older employees are perceived within their organisation. Moreover, stereotypical communication in organisations has negative consequences for the perceived and actual employability of older staff (Henkens 2005) and older workers’ work aspirations (Gaillard and Desmette 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with the content of these stereotypes, recent content analyses have shown that news media portray older employees as warm and incompetent (Kroon, Van Selm, Ter Hoeven & Vliegenthart, in press). These mixed‐media portrayals may contribute to salient stereotypes about older workers, which are thought to underlie age discrimination on the labor market (Van Selm & Van der Heijden, ). Older workers are generally perceived as less employable and have considerable lower re‐employment chances (OECD, ).…”
mentioning
confidence: 99%
“…The study also yields important information for managers, as well as teachers in business programs, seeking to prepare for a changing workforce. The following list offers some suggestions that managers choose to adopt based on the data: Managerial awareness of generationally based stereotypes can be directed toward curbing the reported tendency of intergenerational co-workers to treat one another negatively based on age-based stereotypes (van Selm and Van der Heijden, 2014). This may involve managers reminding employees that they are working with people, not stereotypes. Encourage open dialogue between generational cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…The dangers of such a negative mindset were noted by the research of van Selm and Van der Heijden (2014), who examined some age-based stereotypes of older employees and reflected on how they impinge on co-workers. It is important to recognize, however, that many of the portrayals of Millennials today often come from a mix of popular and business sources whose claims and conclusions are not grounded in empirical study.…”
Section: Millennialsmentioning
confidence: 99%